Differences between urban and rural hedges in England revealed by a citizen science project. Issue 1 (July 2016) - Gosling, Laura; Sparks, Tim; Araya, Yoseph; Harvey, Martin; Ansine, Janice
Abstract Background Hedges are both ecologically and culturally important and are a distinctive feature of the British landscape. However the overall length of hedges across Great Britain is decreasing. Current challenges in studying hedges relate to the dominance of research on rural, as opposed to urban, hedges, and their variability and geographical breadth. To help address these challenges and to educate the public on the importance of hedge habitats for wildlife, in 2010 the Open Air Laboratories (OPAL) programme coordinated a hedge-focused citizen science survey. Results Results from 2891 surveys were analysed. Woody plant species differed significantly between urban and rural areas. Beech, Holly, Ivy, Laurel, Privet and Yew were more commonly recorded in urban hedges whereas Blackthorn, Bramble, Dog Rose, Elder and Hawthorn were recorded more often in rural hedges. Urban and rural differences were shown for some groups of invertebrates. Ants, earwigs and shieldbugs were recorded more frequently in urban hedges whereas blowflies, caterpillars, harvestmen, other beetles, spiders and weevils were recorded more frequently in rural hedges. Spiders were the most frequently recorded invertebrate across all surveys. The presence of hard surfaces adjacent to the hedge was influential on hedge structure, number and diversity of plant species, amount of food available for wildlife and invertebrate number and diversity. In urban hedges with one adjacent hard surface, the food available for wildlife was significantly reduced and in rural hedges, one adjacent hard surface affected the diversity of invertebrates. Conclusions This research highlights that urban hedges may be important habitats for wildlife and that hard surfaces may have an impact on both the number and diversity of plant species and the number and diversity of invertebrates. This study demonstrates that citizen science programmes that focus on hedge surveillance can work and have the added benefit of educating the public on the importance of hedgerow habitats.